AUDIENCE RECEPTION ANALYSIS OF PARENTING EDUCATIONAL CON-TENT ON THE YOUTUBE CHANNEL @NIKITA WILLY OFFICIAL - Nafa Agustina; Siti Muslichatul Mahmudah (Universitas Mercu Buana, 2026)
This research is motivated by the increasing interest in parenting education content on social media, particularly on the YouTube channel Nikita Willy Official. The study focuses on how audiences interpret the parenting content presented on this channel. The purpose of this research is to examine the audience’s understanding of the content and to identify the forms of reception that emerge through the application of Stuart Hall’s reception theory. This research adopts a constructivist paradigm with a qualitative approach and utilizes reception analysis to categorize audience interpretations into three positions: dominant, negotiated, and oppositional. Seven informants were purposively selected as research subjects. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing based on the Miles and Huberman model, supported by source triangulation to ensure data validity. The findings indicate that most informants occupy the dominant position, as they perceive the parenting material presented by Nikita Willy to align with their own parenting values and consider it credible. Others fall into the negotiated position by selectively adopting messages that fit their personal capabilities and circumstances, while a small number hold oppositional views. Overall, Nikita Willy’s parenting content is recognized as an informative, motivating, and beneficial resource for young parents.